2012
DOI: 10.1007/s11192-012-0716-7
|View full text |Cite
|
Sign up to set email alerts
|

Patent litigation precaution method: analyzing characteristics of US litigated and non-litigated patents from 1976 to 2010

Abstract: This study aims to propose an early precaution method which allows predicting probability of patent infringement as well as evaluating patent value. To obtain the purposes, a large-scale analysis on both litigated patents and non-litigated patents issued between 1976 and 2010 by USPTO are conducted. The holistic scale analysis on the two types of patents (3,878,852 non-litigated patents and 31,992 litigated patents in total) issued by USPTO from 1976 to 2010 has not been conducted in literatures and need to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Consistently, previous studies revealed that the number of claims is positively related with the probability of patent litigation (Lanjouw and Schankerman 2001;Su, Chen, and Lee 2012). Therefore, having a high number of claims may positively impact the value of the patent (Gambardella, Harhoff, and Verspagen 2008;Lee et al 2007;Messeni Petruzzelli, Rotolo, and Albino 2015) and its attractiveness within MFTs.…”
Section: Claimssupporting
confidence: 82%
“…Consistently, previous studies revealed that the number of claims is positively related with the probability of patent litigation (Lanjouw and Schankerman 2001;Su, Chen, and Lee 2012). Therefore, having a high number of claims may positively impact the value of the patent (Gambardella, Harhoff, and Verspagen 2008;Lee et al 2007;Messeni Petruzzelli, Rotolo, and Albino 2015) and its attractiveness within MFTs.…”
Section: Claimssupporting
confidence: 82%
“…(van Zeebroeck & van Pottelsberghe de la Potterie, ). From these variables, we can extract valuable information about patents such as technological importance (Carpenter, Narin, & Woolf, ), the existing technological background, the linkage between innovation and basic research (Allison, Lemley, Moore, & Trunkey, ; Allison, Lemley, & Walker, ; Callaert, Van Looy, Verbeek, Debackere, & Thijs, ; Carpenter, Cooper, & Narin, ), the technological scope (Lerner, ; Su, Chen, & Lee, ), the legal breadth of the protection (Lanjouw & Schankerman, ; Marco, ; Nerkar, Paruchuri, & Khaire, ; Tong & Frame, ), and so on.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In the process, first step is to download patent data from USPTO (United States Patent and Trademarks Office). Second, it use model to develop the new model [31]. Third, organization is distinguished for four levels, there are country, industry, company and individual, and each level of organization has specific model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 shows the framework of the innovative service proposed in this study. First, it downloads patent issued from 1976 to 2011 from United States Patent and Trademark Office, and use the forecasting model provided by Su, Chen, & Lee to forecast ligitaiton probability [31].…”
Section: B Expected Function Of the Proposed Intellectual Property Smentioning
confidence: 99%
See 1 more Smart Citation